Adaptive control strategy with parameter optimisation for omni-directional walker. (1st January 2011) - Tan, Renpeng; Wang, Shuoyu; Jiang, Yinlai; Ishida, Kenji; Fujie, Masakatsu G.
In order to support people with walking disabilities to perform walking rehabilitation, an omni-directional walker (ODW) has been developed. Walking training programmes are stored in the walker so that rehabilitation can be carried out without a physical therapist. During walking training the forces imposed by the user's arms to the armrest of the ODW decreased the path tracking accuracy. In a previous study, to address the issue, an adaptive control algorithm was developed to deal with the centre of gravity shift and the load changes caused by the users. However, the control parameters in the non-linear adaptive control law were manually adjusted. In this paper, an adaptive control strategy with automatic parameter adjustment by genetic algorithm is proposed. Simulations are presented to show the feasibility and effectiveness of the proposed scheme.